Polish-Ukrainian Dialogue on the Restitution of Cultural Property Displaced during World War II - Kot, Serhii (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2022)
Negotiations between Ukraine and Poland concerning the return of lost treasures have been ongoing since the beginning of the 1990s. In total, during 1997–2020 six sessions were held of the Intergovernmental Ukrainian-Polish Commission for the Protection and Return of Cultural Property Lost and Illegally Displaced during World War II. However, no cultural objects have been returned to Ukraine or Poland. This article analyzes current Ukrainian-Polish intergovernmental relations on the return and restitution of cultural property lost in consequence of World War II, describes the accomplishments, and examines the problematic issues concerning mutual co-operation.